ANALYZING OF STUDENTS' ATTITUDES TOWARD SCIENCE ON JUNIOR HIGH SCHOOL: Case Study in Muaro Jambi, Indonesia - Dwi Agus Kurniawan; Astalini Astalini; Nugroho Kurniawan (JURNAL PENA SAINS, 2019)
Attitude is expressions of likes or dislikes and expressions of accepting or rejecting an object. This study aims to describe students' attitudes toward science based on three attitude indicators in junior high school in Muaro Jambi. This research study is survey research. The instrument used was a questionnaire that focused on three indicators consisting of 26 statements and also interviews. The sample in this study amounted to 2815 junior high schools in Muaro Jambi.  The results of the study of three indicators’ of attitude, which became the dominant focus of research on the good category. The social implication of science shows a very good category, with a percentage of 53.2%. Enjoyment of science lessons shows a good category with a percentage of 48.1%. Career interest in science is categorized as enough, with a percentage category of 41.8%. Research that has been carried out shows that the attitude of students in junior high school is categorized as good because the three indicators that are examined show good categories.